Clinical and molecular factors for selection of nivolumab or irinotecan as third-line treatment for advanced gastric cancer - Takahiro Ishii; Akihito Kawazoe; Akinori Sasaki; Saori Mishima; Sawada Kentaro; Yoshiaki Nakamura; Daisuke Kotani; Yasutoshi Kuboki; Hiroya Taniguchi; Takashi Kojima; Toshihiko Doi; Takayuki Yoshino; et al. (Therapeutic Advances in Medical Oncology, 2020)
Background: The use of nivolumab or irinotecan as the third-line treatment for patients with advanced gastric cancer (AGC) remains controversial. Methods: This study analyzed patients with AGC treated with nivolumab or irinotecan (nivolumab group or irinotecan group, respectively) from May 2016 to April 2019 following two or more previous lines of chemotherapy. Univariate survival analysis was conducted to identify the clinical and molecular factors associated with progression-free survival (PFS). Results: A total of 156 patients (74 treated with nivolumab and 82 treated with irinotecan) were analyzed. The median PFS was 1.9 months in both treatment groups. The median overall survival (OS) was 7.2 and 6.2 months in the nivolumab and irinotecan groups, respectively. Eastern Cooperative Oncology Group performance status of 1 or more, liver metastasis, a large tumor size at baseline, and HER2-positive status were associated with a worse PFS in the nivolumab group compared with the irinotecan group. The nivolumab group showed a significantly longer PFS (median 3.1 versus 2.0 months) and OS (median 12.9 versus 7.8 months) than the irinotecan group in patients with 0 or 1 of these factors, whereas the irinotecan group showed a significantly longer PFS (median 1.0 versus 1.8 months) and a trend of longer OS (median 3.9 versus 6.1 months) in patients with ⩾2 of these factors. Conclusions: Some clinical and molecular factors were associated with outcomes following nivolumab or irinotecan as the third- or later-line treatment in patients with AGC. These factors must be considered while selecting an optimal treatment option.